Influences of college schooling on the development of moral values as perceived by college teachers and students - Mibolos, Dolly G. L. (1985)
This study aims to determine the perceptions of teachers and students in Nueva Vizcaya tertiary school with regards to the influence of college schooling in developing moral values among students.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Keywords: Values; Moral education